Design and Implementation of IoT-Based Soil Moisture Monitoring and Automatic Irrigation System Using ESP32 - Tasya Sihombing; Maina Lestari Lembong; Asep Arswendi Siburian; Dirjen Berutu (Devitara Innovations, 2026)
Proper soil moisture management plays an essential role in supporting plant growth and improving water-use efficiency. Manual irrigation is still widely practiced and often ignores the actual soil moisture condition, leading to either excessive or insufficient watering. This study aims to design and implement an Internet of Things (IoT)-based soil moisture monitoring and automatic water pump control system using the ESP32 microcontroller. The research employed a Research and Development (R&D) approach through prototype development, including literature review, system requirement analysis, hardware and software design, system implementation, sensor calibration, and performance evaluation. The proposed system integrates a capacitive soil moisture sensor, relay module, 12 V DC water pump, and the Blynk platform for real-time monitoring. A hysteresis control strategy was implemented by setting the lower and upper soil moisture thresholds at 40% and 60%, respectively, to improve pump stability. Experimental results demonstrated that the developed system achieved an average sensor error of 3.42%, an average response time of 2.14 seconds, and maintained soil moisture within the range of 50.9%–54.2% during a seven-day evaluation period. Furthermore, the system reduced water consumption by 31.6% compared with conventional manual irrigation. These findings indicate that the proposed IoT-based system is capable of providing reliable real-time soil moisture monitoring and efficient automatic irrigation, making it suitable for potted plants, home gardens, and small-scale greenhouse applications.